The Construction of Nan Identity in the Context of Globalization through the Festival of Longboat Racing - Kanatham, Suthira (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2021)
The Longboat Racing Festival in Nan Province was the local tradition capable of reflecting the Buddhist way of life and the agricultural society in relation to the river. Past studies did explain Nan and longboat racing tradition, but not in a way that it was analyzed in the broader context. Longboat racing was transformed from festival to sporting events, leading to a change both in the scale and number of participants. Recognition of the festival and national awareness occurred in tandem with an increasing number of interest groups to participate in the festival. Yet, the concept previously used to explain the phenomenon was found insufficient to gain insight of the changes that occur in the present. Therefore, this article aimed to propose a perspective on the tradition invention of the Longboat Racing Festival in Nan Province, using the concepts of Sportization and Localization to demonstrate the complexity of the studied festival, especially during the past decade. The insights were obtained from the interviews conducted with the stakeholders; government organizations, private and civil sectors, which led to the finding that Nan's longboat racing festival functioned as the space where the actors were open to improve social relationships. The tension arising from the contention for meaning and negotiation of power to control the festival was a means of developing capacity to redefine the Nan local identity in an ever-changing global context. The effort to sportize the longboat racing festival was one of the channels to add “value” to local Nan and Nan people, which promoted Nan Province to the international level.